Factors associated with loss learning recovery after the COVID-19 pandemic of students in Nakhon Si Thammarat, Thailand - Ratmanee, Yodfah; Borirakarawin, Manorot; Pollar, Manit; Keeratipattarakarn, Kanitta; Kiatikongkiri, Ampa (International Journal Of Community Medicine And Public Health, 2023)
Background: The southern province of Thailand, Nakhon Si Thammarat, has the greatest amount of schools. The COVID-19 outbreak has had a major impact, notably on students who have missed out on their education as a result of the prolonged closure of the schools to stop the spread. It is very important to investigate the effect of socio-demographic factors on the loss learning recovery of student in primary schools. This study aimed to explore the influencing factors of student in primary schools based on their socio-demographic status. Methods: The analysis utilized secondary data from observations of student behavior collected by school teachers in May 2021 and April 2022. Chi-square test, ANOVA test, and multiple-linear regression were used to examine the factors. Results: The results showed that the loss learning recovery significant difference with marital status of parents and family income. The group of parents who had marital status of married had the higher loss learning recovery than divorced as well as the group of low income family had the lowest loss learning recovery. Conclusions: It is necessary to understand the characteristics of the student in primary school. Especially factors that affect the loss learning recovery for build education systems back better and found to support them in every manner so that their learning can resume normally and advance past what was lost.